Decoding the ovary-thyroid connection: a case report on intricacies of untreated hypothyroidism - Jose, Meenu; Madhavan, Sheeja; Menon, Hridya (International Journal of Contemporary Pediatrics, 2024)
Precocious puberty may be a rare presentation of untreated hypothyroidism, while delayed puberty is its norm. Van Wyk-Grumbach syndrome (VWGS) refers to the development of isosexual precocious pseudo puberty and multicystic enlarged ovaries in the presence of hypothyroidism. Here we report a case of an eight-year-old girl child who required emergency surgical intervention attributable to the aforementioned syndrome.